2017
DOI: 10.4317/jced.53630
|View full text |Cite
|
Sign up to set email alerts
|

Juxtacortical Mandibular Chondrosarcoma during pregnancy: A case report

Abstract: Chondrosarcoma is one of the most common malignant bone tumors in adults. It use to affect upper arm, pelvis and thigh bone. A wide surgical extirpation represent the gold standard to treat this disorder. In fact, radiotherapy and chemotherapy are no useful. Interestingly, chondrosarcoma is rare in head and neck (HNCS) and extremely uncommon during pregnancy. Thus, there is a lack of evidence about the proper treatment in these cases. A wide surgical extirpation is also considered the most effective procedure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It has also been suggested that primary pure heterologous sarcomas may arise from primitive embryonal cell remnants or from a complete stromal overgrowth of a Mullerian mixed tumor. Another etiology appears to be related to the uncontrolled proliferation of Merkel cells (embryonic remains) [1,2]. Chondrosarcoma is also uncommon during pregnancy, and to the best of our knowledge no cases of proven primary ovarian chondrosarcoma in pregnancy have been reported in the literature; with regard to chondrosarcoma arising primarily in the ovary, only two cases have been reported in the English-language literature [6].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that primary pure heterologous sarcomas may arise from primitive embryonal cell remnants or from a complete stromal overgrowth of a Mullerian mixed tumor. Another etiology appears to be related to the uncontrolled proliferation of Merkel cells (embryonic remains) [1,2]. Chondrosarcoma is also uncommon during pregnancy, and to the best of our knowledge no cases of proven primary ovarian chondrosarcoma in pregnancy have been reported in the literature; with regard to chondrosarcoma arising primarily in the ovary, only two cases have been reported in the English-language literature [6].…”
Section: Discussionmentioning
confidence: 99%
“…The effect of pregnancy on the growth features of chondrosarcomas remains unclear. Some experts have suggested a growth-enhancing effect of altered hormone levels on various bone tumors during pregnancy [2]. In addition, it still remains unclear whether chondrosarcoma during pregnancy may show progression or dedifferentiation according to the changes in hormonal status [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 169 articles were subjected to full-text evaluation. After comprehensive review, 161 articles were excluded, leaving 8 articles as eligible for final inclusion in this systematic review[12][13][14][15][16][17][18][19].…”
mentioning
confidence: 99%